Pyrotechnic Mixtures For the Production of Colored Smoke - Zeman, Ondřej (Univerzita Pardubice, 2021)
The thesis is focused on the research and testing of pyrotechnic compositions, precisely coloured smoke compositions. Pyrotechnic smoke compositions for production of red smoke are emphasised. From literary research, some of the organic dyes are chosen to be examined as suitable smoke colouring agents. The dyes are tested in a traditional fuel/oxidizer system and different, less used, systems.
Pyrotechnické slože pro přípravu barevného dýmu
Keywords: pyrotechnická slož; dýmovnice; barevný dým; organická barviva; dýmová slož; pyrotechnic composition; smoke grenade; coloured smoke; organic dyes; smoke composition